Keynes's "Finance" Demand for Liquidity, Robertson's Loanable Funds Theory, and Friedman's Monetarism - Tsiang, S. C. (Quarterly Journal of Economics, 1980)
This paper argues that Keynes's concession on the finance demand for liquidity provides the key for the reconciliations of the liquidity preference theory to the loanable funds theory and of the stock approach with the flow approach. On many practical issues, Robertson is shown to be right, and Keynes wrong. It also shows that the modern arch-critic of Keynes, Friedman, is himself under Keynes's influence in relying exclusively upon the stock (or portfolio) approach to the neglect of the influences of flow decisions on the money demand. His attempt to combine Keynes and Fisher is shown not workable.